The diagnostic performance of platelet function analyzer-100 (PFA-100) in Thai children with mucocutaneous bleeding disorder - Narin Khongjaroensakun; Karan Paisooksantivatana; Ampaiwan Chuansumrit; Pakawan Wongwerawattanakoon; Praguywan Kadegasem; Nongnuch Sirachainan (Pediatric Hematology Oncology Journal, 2022)
Background: Closure time (CT), a parameter measured by platelet function analyzer (PFA-100), is used to assess primary hemostasis. However, some factors (e.g., ethnicity and age) may affect its cut-off value or reference range. Moreover, the diagnostic performance of CT in the Thai and Southeast Asian populations has not been reported in any study. Therefore, this study aims to evaluate the diagnostic performance of CT in patients with mucocutaneous bleeding disorder using the established cut-off value from Thai children. Methods: CT from both collagen/epinephrine (COL/EPI) and collagen/adenosine 5- diphosphate (COL/ADP) cartridges and complete blood count were performed in both healthy volunteers and known cases of primary hemostatic disorders. The cut-off value and diagnostic performance of CT was determined using receiver operating characteristic curve analysis. Results: The cut-off value of both COL/EPI and COL/ADP in this study was somewhat prolonged than the other studies because of the higher prevalence of non-responsiveness of platelets to epinephrine stimulation in the Asian than the Western. Nonetheless, the diagnostic performance was comparable to the previous studies. In addition, the diagnostic performance could be enhanced when the CT from both cartridges was interpreted together. Conclusion: The cut-off value in this study was more prolonged than in other studies due to the variation of ethnicity. Consequently, each laboratory should establish and/or verify its own CT reference range prior to use in clinical practice. Furthermore, CT interpretation of both cartridges together resulted in a better diagnostic performance than interpreting each cartridge separately.